Long-Term Outcomes of Patients With Cocaine Use Disorder: A 18-years Addiction Cohort Study - Sanvisens, Arantza; Hernández-Rubio, Anna; Zuluaga, Paola; Fuster, Daniel; Papaseit, Esther; Galan, Sara; Farré, Magí; Muga, Robert (Frontiers in Pharmacology, 2021)
Objective: Cocaine Use Disorder (CUD) has been associated with multiple complications and premature death. The purpose of the present study was to analyze the relationship between baseline medical comorbidity and long-term medical outcomes (i.e., hospitalization, death) in a cohort of patients primarily admitted for detoxification. In addition, we aimed to analyze cause-specific mortality. Methods: longitudinal study in CUD patients admitted for detoxification between 2001 and 2018. Substance use characteristics, laboratory parameters and medical comorbidity by VACS Index were assessed at admission. Follow-up and health-related outcomes were ascertained through visits and e-health records. Kaplan-Meier and Cox regression models were used to analyze survival and predictors of hospitalization and death. Results: 175 patients (77.7% men) were included. Age at admission was 35 years [IQR: 30-41 years], 59.4% of the patients being intranasal users, 33.5% injectors, and 7.1% smokers. Almost 23% of patients had concomitant alcohol use disorder, 39% were cannabis users and 9% opiate users. The median VACS Index score on admission was 10 points [IQR: 0-22]. After 12 years [IQR: 8.6-15 years] of follow-up there were 1,292 (80.7%) ED admissions and 308 (19.3%) hospitalizations. The incidence rate of ED admission and hospitalization was 18.6 x100 p-y (95%CI: 15.8-21.8 x100 p-y). Mortality rate was 1.4 x100 p-y (95%CI: 0.9-2.0 x100 p-y) and, baseline comorbidity predicted hospitalization and mortality: those with VACS Index >40 were 3.5 times (HR:3.52, 95%CI: 1.19-10.4) more likely to dye with respect to patients with VACS <20. Conclusion: addiction care warrants optimal stratification of medical comorbidity to improve health outcomes and survival of CUD patients seeking treatment of the disorder.